Elotuzumab: the first available immunotherapeutic arrow against relapsed-refractory Multiple Myeloma - Offidani, Massimo; Corvatta, Laura (European Journal of Oncology and Environmental Health, 2017)
The recent introduction of second-generation proteasome inhibitors such as carfilzomib and ixazomib and new immunomodulatory agents such as lenalidomide and pomalidomide has led to advances in the treatment of patients with relapsed/refractory Multiple Myeloma (MM). However, the discovery of several new targets on myeloma cells, has led to the use of monoclonal antibodies that have proved a promising approach in these patients. Elotuzumab, the first monoclonal antibody to be evaluated in phase 3 trial, directed against SLAMF7, induces myeloma death by direct activation of natural killer cells and via antibody-dependent cell-mediated cytotoxicity. In this paper, the main findings of the combination Elotuzumab-lenalidomide-dexamethasone in relapsed-refractory MM will be summarized.